A New geographical dictionary v.2 - London, Printed for J. Coote (London, Printed for J. Coote, 1759)
A New geographical dictionary. This containing a full and accurate account of the several parts of the known world, as it is divided into continents, islands, oceans, seas, rivers, and lakes. As well as the situation, extent, and boundaries, of all the empires, kingdoms, states, provinces & in Europe, Asia, Africa, and America. Together with the religion, learning, policy, manners, and customs, of the inhabitants. To which is prefixed, an introductory dissertation, explaining the figure and motion of the earth. Illustrated with a new and accurate set of maps of all the parts of the known world, making a complete atlas. The dresses of the inhabitants, and a great variety of plans and perspective views of the principal cities, towns, harbors, structures, ruins, and other places of antiquity.
A New geographical dictionary. Containing a full and accurate account of the several parts of the known world, as it is divided into continents, islands, oceans, seas, rivers, lakes
Volume two of two. Both containing illustrations, maps, and description of plans.
Keywords: rare books, dictionary, geography, geographical dictionary